Coal production capacity allocation based on efficiency perspective—taking production mines in Shandong Province as an example. (December 2022) - Wang, Xiaofei; Miao, Chenglin; Wang, Chongmei; Yin, Dawei; Chen, Shaojie; Chen, Lei; Li, Ke
Abstract: Coal remains an irreplaceable main energy source in China. This paper uses the zero-sum gain data envelopment analysis (ZSG-DEA) model, and proposes a production capacity optimization allocation plan, which provides a theoretical basis for how to ensure energy security in the context of China's dual-carbon strategy. Results show: (1) the optimal plan adjusts the production capacity by 7.32 million tons/year, accounting for 6.33% of the total production capacity; 32 mines will be increased in production capacity, and 19 mines will be reduced in production capacity. (2) Under the optimal plan, the raw coal output, income, and profit of provincial coal mines will increase by 3.5965 million tons, 2.65 billion yuan, and 0.972 billion yuan, respectively, and wages are expected to decrease by 73.5 million yuan. (3) In terms of the fairness of personnel placement, the Gini coefficient of the actual situation is 0.3082, and that of the optimal scheme is 0.2896. It suggests that engaging in the "one size fits all" campaign of marginalization and coal decoalization is unadvisable. Coal supply and market demand should be efficiently connected, and the elimination of backward production capacity and the release of advantageous production capacity should be rationally coordinated. Highlights: Propose the optimal allocation scheme of coal stock production capacity. Evaluate the economic benefits and fairness of the optimal allocation scheme. Provide reasonable policy recommendations to ensure national energy security.